Transparansi Pelaporan Keuangan: Apakah Berdampak terhadap Penghindaran Pajak dan Nilai Perusahaan - Ningtias Safitri; Dahlia Sari (ITB AAS INDONESIA, 2021)
This purpose of this study is to examine the effect of transparency on tax avoidance, the effect of tax avoidance on firm value, and the effect of transparency on relationship between tax avoidance on firm value. The sample of this study consists of 66 manufacture companies during the period of 2010-2014, with 330 total observation. The results showed that company transparency with a proxy accrual discretion and audit quality would reduce tax avoidance. It means the higher the company's transparency, the lower the tax avoidance. The results showed that tax avoidance did not affect firm value. It probably due to tax avoidance that can be interpreted as negative, positive, or neutral information by investors. The results showed that corporate transparency did not affect the relationship between tax avoidance and firm value. This result shows that investors have not seen corporate transparency as a positive signal for the valuation of company shares. The contribution of this research is to use a comprehensive proxy in measuring financial transparency, namely earnings quality, audit quality, and stock trading volume. This research implies that financial transparency or disclosure of corporate financial information is not proven to be used by investors in determining investment